HIDUP SETELAH MENIKAH, MENGURAI EMOSI POSITIF DAN RESILIENSI PADA WANITA TANPA PASANGAN - Sholichatun, Yulia (Pusat Studi Gender UIN Maulana Malik Ibrahim Malang, 2009)
Divorce and the death of spouse can be a painful and sometimes delibitating experiences.However, bereaved individuals differ markedly in how much and how long they grieve.positives emotions may be most benefecial, however when they are at the time of stress. Positive emotions contribute to psychological well-being via more effective coping. The experience of positive emotiopns functions to assist reilient individuals in their ability to recover effectively from bereavement.